Theology as dialogue and fragment: saying God with David Tracy - Palfrey, B (2013)
This thesis concerns the ideas of ‘dialogue’ and ‘fragment’ in the work of the American liberal Roman Catholic theologian David Tracy (bn. 1939). Dialogue (or ‘conversation’) established itself as a dominant idea for Tracy in the 1980s, whereas the centrality of fragments first emerged for Tracy in the late 1990s, to complicate and refine his earlier thinking. Despite this historical sequence, however, the organisation of this thesis is thematic rather than essentially chronological. The first three chapters focus on how in the later 1970s and 1980s Tracy adapted his ideas of conversation-dialogue from the thought of the German philosopher Hans-Georg Gadamer. Chapter Four examines some serious objections to Tracy’s concept of dialogic reason, before defending his basic choices and gesturing towards his more recent work as perhaps resolving real previous difficulties. Chapter Five explores the ‘ontological`’ thinking of Martin Heidegger, valuable for evaluating Tracy despite the latter’s determination to put his own thinking on a more empirical and pluralistic footing. Chapter Six tackles this theme of Tracy’s ongoingly ‘empirical’ sensibility, as well as the importance he has attached to the experiencing human ‘self.’ Tracy’s ideas of human experience and selfhood owe much to William James and to Bernard Lonergan. Chapter Seven examines ‘correlational’ concepts that Tracy has forged to facilitate Christian theology over the course of his career since Blessed Rage for Order (1975). As Tracy became philosophically and theologically uncomfortable with theism as the supposed essential horizon for theology (around 1990), so the idea of the ‘mystical-prophetic’ emerged to open a door into new horizons of thinking. Chapter Eight highlights an easily overlooked antecedent of the hermeneutical negativity that Tracy’s recent ideas of ‘fragments’ imply: in Gadamer’s sense of the Christina negative ‘sign’ of the Ecce Homo. Chapter Nine then focuses on Tracy’s ideas of thinking through fragments: their adequacy and possible consequences.